2019
DOI: 10.3390/w11040703
|View full text |Cite
|
Sign up to set email alerts
|

Pan-European Calculation of Hydrologic Stress Metrics in Rivers: A First Assessment with Potential Connections to Ecological Status

Abstract: The hydrologic regime of a river is one of the factors determining its ecological status. This paper tries to indicate the present hydrologic stress occurring across European rivers on the basis of model integration. This results in a pan-European assessment at the resolution of the functional elementary catchment (FEC), based on simulated daily time-series of river flows from the model PCR-GLOBWB. To estimate proxies of the present hydrologic stress, two datasets of river flow were simulated under the same cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Hydrological stressor data were generated with the global model PCR‐GLOBWB (Sutanudjaja et al, 2018). Two datasets of daily time series of river discharges covering the period 2001–2010 were simulated under the same climate (Panagopoulos et al, 2019). The first dataset resulted from a least‐disturbed condition scenario, excluding all water uses such as irrigation, abstractions, industry or water management as well as the presence and hydrological impacts from reservoirs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrological stressor data were generated with the global model PCR‐GLOBWB (Sutanudjaja et al, 2018). Two datasets of daily time series of river discharges covering the period 2001–2010 were simulated under the same climate (Panagopoulos et al, 2019). The first dataset resulted from a least‐disturbed condition scenario, excluding all water uses such as irrigation, abstractions, industry or water management as well as the presence and hydrological impacts from reservoirs.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, we expected nutrient enrichment to be particularly relevant for the ecological status of lowland rivers, whose catchments are often characterized by high agricultural intensities (Hypothesis 2.1; e.g. Lemm & Feld, 2017); hydrological alteration to be particularly relevant for river types with small and F I G U R E 1 Overview of the locations of 52,847 sub-catchment units and their ecological status class (grey area: no data available) medium size catchments or rivers in the Mediterranean, which are frequently affected by damming or water abstraction for irrigation (Hypothesis 2.2;Couto & Olden, 2018;Huđek et al, 2020;Panagopoulos et al, 2019); and toxic substances to mainly affect small streams in intensively used areas (Hypothesis 2.3;Beketov et al, 2013;Schäfer et al, 2013). We furthermore expected that riparian land use particularly impacts ecological status of small streams, which are more strongly affected by the immediate surrounding as compared to larger rivers, for which cumulative stressors at catchment scale are more relevant (Hypothesis 2.4;Fuller & Death, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported declining river flows and changes in the water quantity during the past decades [57,58], but it remains unclear how reducing precipitation is linked with hydrological alterations. This is more prominent in the Mediterranean since river damming and water abstractions are major environmental problems that are responsible for changing flow patterns and reduced water quantity [59][60][61]. For instance, Mentzafou et al [57] showed significant relationships between precipitation and discharge with similar fluctuation patterns for major Greek rivers but concluded that a more in-depth analysis that considers the water uses will reveal the actual causes of flow regime changes.…”
Section: Implications Of Precipitation Variability On Inland Freshwat...mentioning
confidence: 99%
“…Since dissolved oxygen concentration is inversely related to water temperature, warming is expected to affect dissolved oxygen saturation (Cox and Whitehead 2009). Additionally, hypoxia in running waters may occur not only because of organic pollution and eutrophication but also due to drought and extreme low flow events, conditions that are becoming more common in Southern Europe (Gudmundsson et al 2017;Panagopoulos et al 2019). We acknowledge that such complexities will be difficult to resolve in our modelling approach, not least because of the potential for covariance between stressors.…”
Section: Effects Of Multiple and Interacting Stressors On Each Demons...mentioning
confidence: 99%